CLINICAL EFFICIENCY OF ZINC PYRITHIONE TO TREAT ATOPIC DERMATITIS IN CHILDREN - D.S. Korostovtsev; A.N. Pampura; R.S. Fassakhov; E.O. Sukmanskaya; F.I. Petrovsky (Педиатрическая фармакология)
Atopic dermatitis is one of the most widespread children’s diseases, it has a chronic recurrent clinical course, may be often complicated with the secondary infection. This necessitates the choice of a medication to impact all stages of the disease process with a high safety profile. This digest is devoted to activated zinc pyrithione. Overall, currently available data make it possible to state that this agent is one of the most effective and safest products to be used for a local therapy of atopic dermatitis in children. Key words: atopic dermatitis, activated zinc pyrithione, children